About Professor Ilona Czamańska - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 2022)
Occasional text devoted to professor Ilona Czamańska, on the occasion of the Her 70th birthday anniversary. The autor discusses the scentific achievements of the Jubilarian the field of her research in the area of the Balcan Peninsula.